If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(2x + -3) + 2(6x + 2) = 2(x + 1) Reorder the terms: 6(-3 + 2x) + 2(6x + 2) = 2(x + 1) (-3 * 6 + 2x * 6) + 2(6x + 2) = 2(x + 1) (-18 + 12x) + 2(6x + 2) = 2(x + 1) Reorder the terms: -18 + 12x + 2(2 + 6x) = 2(x + 1) -18 + 12x + (2 * 2 + 6x * 2) = 2(x + 1) -18 + 12x + (4 + 12x) = 2(x + 1) Reorder the terms: -18 + 4 + 12x + 12x = 2(x + 1) Combine like terms: -18 + 4 = -14 -14 + 12x + 12x = 2(x + 1) Combine like terms: 12x + 12x = 24x -14 + 24x = 2(x + 1) Reorder the terms: -14 + 24x = 2(1 + x) -14 + 24x = (1 * 2 + x * 2) -14 + 24x = (2 + 2x) Solving -14 + 24x = 2 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -14 + 24x + -2x = 2 + 2x + -2x Combine like terms: 24x + -2x = 22x -14 + 22x = 2 + 2x + -2x Combine like terms: 2x + -2x = 0 -14 + 22x = 2 + 0 -14 + 22x = 2 Add '14' to each side of the equation. -14 + 14 + 22x = 2 + 14 Combine like terms: -14 + 14 = 0 0 + 22x = 2 + 14 22x = 2 + 14 Combine like terms: 2 + 14 = 16 22x = 16 Divide each side by '22'. x = 0.7272727273 Simplifying x = 0.7272727273
| 3y+3(1-y)-y=10 | | (2x-5)+15=67 | | 6(y-5)=4(4+y) | | -2x^2+5x+33=21 | | b+21/6=-13/8 | | -2x^2+5x+33=0 | | 6(4-5)=4(4+y) | | -5(2b+7)-7(-b-8)=0 | | 4x+5y=19 | | 2x^2-5x-33=21 | | 3y^2+7=2y | | 6y-30=16+4y | | -48=6(-6h-2) | | 4(2x-5)15=67 | | 7ln(2x+5)=8 | | 4x+5x=19 | | -8+6p=4(7+6p) | | k/100=0.15 | | 9+9n=-162 | | -(7b+7)=-14 | | k/20=0.15 | | k/8=6 | | 8x+12=11X | | g/2=16 | | -22-7n=-6+3(1-2n) | | -6y+9+4y=13 | | 8f=24 | | -3(1x+4)=-4x | | 4a^2+9a+1=0 | | x^2+3x+2=7 | | 5=-7y | | 4y-2=90 |